FILSAFAT AKHLAK DALAM PEMIKIRAN IBNU MISKAWAIH DAN AL-GHAZALI (STUDI KOMPARATIF) - Ummul Latifa; Nelmaya Nelmaya (Jurnal Salome : Multidisipliner Keilmuan, 2024)
One of the main missions in Islam is to perfect human morals. Morals are very important and fundamental, because with morals can be determined the measure of all human actions, good bad, right wrong, halal and haram. Humans without morals will lose their human dignity as the most noble creatures of Allah. In this case, Ibn Miskawaih and Al-Ghazali expressed their opinions regarding the Philosophy of Morals, having the same opinion regarding the investigation of Morals must begin with knowledge of the soul, its strength and even its characteristics. The type of research used is qualitative research which is library research. The primary data sources were obtained from the library books by Ibn Miskawaih "Towards the Perfection of Morals: The First Book of Daras Regarding the Philosophy of Ethics, and Al-Ghazali Ihya Ulumuddin, Menyikawat Rahasia Keajaiban Hati". This study uses a philosophical approach. In data management, the historical continuity method, analytical descriptive method, and data interpretation method were used. This study has produced conclusions. Morals according to Ibn Miskawaih are a condition of the human soul that spontaneously drives him to do an act without thinking and hesitation. While Morals according to Al-Ghazali are traits embedded in the soul from which actions arise easily without requiring prior consideration. The virtues of Morals consist of wisdom, simplicity, courage, and justice. Moral Education according to Ibn Miskawaih is education that is focused on leading humans in a better direction. While Moral Education according to Al-Ghazali is a process of forming an ideal personality.